FEATURES OF CREATING NEWS IN THE CAMPUS INFORMATION SYSTEM - Ternovyy, Ivan; Khamula, Orest (Collection of scientific papers «ΛΌГOΣ», 2024)
In dormitories, there is often a problem of spreading important news. Wall paper posters are used for this. Their disadvantage is that they are easily missed by students in a hurry. Therefore, it is necessary to create a system of effective news production, that is, to develop a page on which all news will be displayed, as well as the ability to create important news for display on the main page of the site.